BAHAN AJAR DIGITAL MEMBACA TEKS CERITA RAKYAT KALIMANTAN TENGAH BERMUATAN PENDIDIKAN KARAKTER DAN LITERASI KRITIS - Indra Perdana; Glory Kriswantara (Balai Bahasa Sulawesi Selatan, 2021)
This research is devoted to producing digital teaching materials that support the ability to read with critical thinking. The product output is an Android-based Flipbook digital book. This digital book contains teaching materials for reading Central Kalimantan folklore with character to build a culture of critical literacy for students. This type of Research Development (RD) conducted by researchers is the result of adaptation of the theory of Borg and Gall. The adopted procedure was then simplified into five, namely: 1) analysis of teaching material needs; 2) product development in the form of an android based digital flipbook; 3) validation test by expert; 4) product revision, and 5) product trial. This research was conducted at SMA Negeri 6 Palangka Raya with the research subjects being class X students in the 2021/2022 academic year. Sources of data from this study were obtained through interviews and questionnaires to teachers and students. The collected data were analyzed using descriptive statistics. The results of the validation of the Indonesian language teacher obtained an average score of 3.65 from the aspect of content/material, language, presentation, graphics and media with a percentage of 73%. After the product developed entered the revision stage, a trial was conducted on 30 students of class X Bahasa for the 2021/2022 academic year at SMAN 6 Palangka Raya. The score obtained from the five aspects tested is 4.2 with an 84% achievement percentage. Based on field tests, the product in the form of a digital flipbook of Central Kalimantan folklore based on Android has met the criteria for supporting critical literacy, has character, is practical, and is effectively used in learning. Keywords: digital teaching materials, folklore, critical literacy Abstrak Penelitian pengembangan ini dikhususkan untuk menghasilkan produk bahan ajar digital yang menunjang kemampuan membaca dengan pemikiran yang kritis. Luaran produk berupa buku digital Flipbook berbasis android. Buku digital ini memuat bahan ajar membaca cerita rakyat Kalimantan Tengah yang bermuatan karakter untuk membangun budaya literasi kritis siswa. Penelitian berjenis pengembangan atau Research Development (R D) yang diusung peneliti adalah hasil adaptasi dari teori Borg dan Gall. Prosedur yang diadopsi kemudian dilakukan penyederhanaan menjadi lima, yaitu: 1) analisis kebutuhan bahan ajar; 2) pengembangan produk berupa buku digital flipbook berbasis android; 3) uji validasi oleh ahli; 4) revisi produk, dan 5) ujicoba produk. Penelitian ini dilakukan di SMA Negeri 6 Palangka Raya dengan subjeknya adalah siswa kelas X tahun pembelajaran 2021/2022. Sumber data dari penelitian ini diperoleh melalui wawancara dan angket terhadap guru serta siswa. Data yang terkumpul dianalisis dengan menggunakan statistik deskriptif. Hasil validasi dari guru bahasa Indonesia diperoleh skor rata-rata 3,65 dari aspek isi/materi, bahasa, penyajian, grafis dan media dengan persentase 73%. Setelah produk yang dikembangkan memasuk tahap revisi, dilakukanlah ujicoba terhadap 30 orang siswa kelas X Bahasa tahun pembelajaran 2021/2022 SMAN 6 Palangka Raya. Perolehan skor dari kelima aspek yang diuji adalah 4,2 dengan capaian persentase 84%. Berdasarkan uji lapangan, produk berupa buku digital flipbook cerita rakyat Kalimantan Tengah berbasis android telah memenuhi kriteria menunjang literasi kritis, bermuatan karakter, praktis, dan efektif digunakan dalam pembelajaran. Kata-kata kunci: bahan ajar digital, cerita rakyat, literasi kritis